An exploratory review of pre-qualification interprofessional education evaluations. Issue 4 (July 2015) - Thistlethwaite, Jill; Kumar, Koshila; Moran, Monica; Saunders, Rosemary; Carr, Sandra
Abstract There are diverse perceptions about the primary purpose of evaluation. In interprofessional education (IPE), there has been a perceived focus on evaluating against the outcome of improved collaborative practice and quality of care. This paper presents an exploration of the nature and purpose of evaluation methods commonly utilized in the IPE literature with its focus on outcomes-based evaluation and particularly the Kirkpatrick framework. It categorises recent evaluations of pre-qualification (pre-certification) IPE interventions. Of the 90 studies included, most evaluated soon after the educational intervention, only five specifically referred to an evaluation framework and the most frequently used tool was the RIPLS. There was a noteworthy reliance on students' self-rated perceptions of their attitudes towards collaborative practice collected through surveys, focus groups and interviews. There appears to be a need to reconsider the type of evaluation required. In conclusion, this paper offers recommendations for evaluation practice that is moving towards realist approaches; describes the longer term effects of interventions on attitudes and behaviour; develops and validates data collection tools including direct observation of practice and more comprehensively engages with all stakeholders to ensure that evaluation activities are not only focused on improving IPE but also on enhancing our understanding of interprofessional practice.